EKSPLORASI CENDAWAN ENTOMOPATOGEN PADA LAHAN GAMBUT - Astrid Sebayang; Tris Haris Ramadhan; Zakiatulyaqin Zakiatulyaqin (Fakultas Pertanian Universitas Tanjungpura, 2022)
The use of entomopathogenic fungus as an alternative pest control is an attempt to reduce the use of synthetic pesticides that have caused many environmental problems. The aim of this reasearch is to know kinds of entomopathogenic fungus that endemic of Kalimantan Barat peat soil. This research used descriptive methods which as exploration of peat soil fungus on several locations in West Kalimantan are Rasau Jaya, Siantan and Tanjungpura University forest. Entomopathogenic fungus was obtained by trapping which apply on Tenebrio molitor larvae and isolation of peat soil. Pathogenecity of entomopathogenic fungus has been tested on T. molitor larvae. Three fungus were explored, namely Trichoderma harzianum, Aspergillus niger, and x fungi which have not been identified, have low power to kill the larvae of T.molitor on several concentration level of those suspension fungus.